Analyzing the Biochemical Alterations and Histopathological changes in Oxidative Stress-Induced Tissue Damage. A Study on Antioxidant Therapeutic Interventions - Fahmida Khatoon, Aaisha Qadir, Kiran Memeon, Rubina Shafi, Masud Ali Ansari, Qandeel Abbas Soomro, Muhammad Nasir Shahbaz, Arslan Shuja, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hexavalent chromium [Cr (VI)] is a toxic industrial chemical that produces oxidative stress, disrupts biochemical pathways, and causes severe organ damage. Objectives: The study aimed to assess the dose and time-dependent biochemical and histopathological effects of hexavalent chromium [Cr (VI)] exposure, including oxidative stress, hepatotoxicity, and nephrotoxicity. Methodology: The effects of hexavalent chromium (Cr (VI)) were evaluated on albino rats over 30, 60, and 90 days, at dose and time-dependent conditions. Control and treatment groups (2, 5, and 10 mg/kg [Cr (VI)] were given daily orally to rats. The analysis of oxidative stress markers (MDA, GSH, SOD), liver enzymes (ALT, AST), and renal parameters (creatinine, BUN) was carried out. For formalin fixation and staining, liver and kidney tissues were subjected to histopathological examination. One-way ANOVA (p < 0.05) significance was used in statistical analysis, adhering to ethical and international guidelines. Results: Dose and time dependence of oxidative stress and organ damage were produced after exposure to hexavalent chromium [Cr (VI)]. Decreased glutathione (GSH) and superoxide dismutase (SOD) activity, increased blood levels of lipid peroxidation products, and higher malondialdehyde (MDA), a sign of lipid peroxidation, were demonstrated. Levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), creatinine, and blood urea nitrogen (BUN) were high, indicating hepatocellular damage and renal impairment, respectively, and suggesting systemic toxicity and increasing oxidative damage. Conclusion: Dose and time-dependent oxidative stress (increased lipid peroxidation and decreased antioxidant defenses), causing hepatocellular and renal dysfunction, results from exposure to hexavalent chromium [Cr (VI)]. These results also serve to further demonstrate the cumulative toxicity of [Cr (VI)] and its ability to disrupt biochemical and histopathological homeostasis. Keywords: Hexavalent chromium, malondialdehyde, glutathione, superoxide dismutase, alanine aminotransferase, aspartate aminotransferase.